Autonomous drone warfare - Martín Carbajo-Núñez OFM (Warszawskie Studia Teologiczne)
Recently, a military robot has autonomously taken the decision to attack enemy troops in the Libyan war without waiting for any human intervention. Russia is also suspected of using such kind of robots in the current war against Ukraine. This news has highlighted the possibility of radical changes in war scenarios. Using a Catholic perspective, we will analyze these new challenges, indicating the anthropological and ethical bases that must lead to the prohibition of autonomous “killer robots” and, more generally, to the overcoming of the just war theory. We will also point out the importance of Francis of Assisi, whom the encyclical Fratelli tutti has proposed again as a model for advancing towards a fraternal and pacified humanity.